ミズホ カンソク キョテン ニオケル チジキ ミャクドウ カンソク ホウコク ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 福西, 浩; フクニシ, ヒロシ; FUKUNISHI, Hiroshi (国立極地研究所, 1973)
P(論文) Continuous observations of geomagnetic pulsations were carried out from July 20 to 29, 1970 at Mizuho Camp which had been established by the llth wintering party of the Japanese Antarctic Research Expedition as a scientific observatory in the Antarctic inland area. The geomagnetic pulsations were measured with an induction magnetometer and were recorded simultaneously using both a PWM data recorder and a pen-oscillograph. Similar observations were made at Syowa Station which is about 300 km northwest of Mizuho Camp. By comparing the data from these two stations, it is noticed that PC 2, 3 and Pi 1 pulsations usually occur concurrently at both the stations, whereas Pi bursts often occur at only one station, suggesting that the occurrences of Pi bursts are restricted within small area. departmental bulletin paper